Nilai-Nilai Aliran Kebatinan Perjalanan dan Dasar Negara - Ilim Abdul Halim (UIN Sunan Gunung Djati Bandung, 2016)
This study argues that existence of the phenomenon of the rise of Sundanese culture can not be separated from the system itself Sundanese community trust formed by faith and history. Study of psychotherapy cult journey in the context of Indonesia is based on Pancasila considered important as the framework and work in maintaining national integration. Kebatinan flow trip is not only seen as a culture but can also be understood as a religion, because religious elements contained in the flow of mysticism that trip. In kebatinan trips are shared values that cageur, bageur, right, smart and safe. The values of religious sourced from wangsit used as a way to understand the Pancasila as the state